CHARACTERIZATION OF A SIDDHA DRUG (PÅ¨RNA CANTIROTAYA CENTÅ¨RAM): AN APPROACH TO STANDARDIZATION - CHITRA B,; RAMASWAMY RS,; SHAKILA R, (International Journal of Pharma and Bio Sciences, 2015)
Siddha system of medicine is existing among the indian society since time immemorial. However, in spite of their efficacy, they have been widely criticized due to lack of standardization and their complex preparation methods. The present study was designed as a step towards standardization of the herbo-metallic formulation, PÅ©rna Cantirotaya CentÅ©ram (PCC). To assure the quality of PCC, the drug was subjected to physico-chemical parameters as mentioned in PLIM guidelines, Xâ€‘Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) and Energy Dispersive analysis of X-ray (EDAX). The SEM study revealed that the particles in the formulation are agglomerated. The particle size varied between 1 and 10 μm. EDAX study indicated that the drug contains mercury, sulphur, gold, sodium, potassium, calcium, carbon and oxygen in major percentage and magnesium, aluminium, silicon, iron and niobium in minor percentage. It is concluded that PCC is a complex compound, having very small particle size and essential elements that might be the reason for its wide ranging clinical efficacy.